KONSELOR DAN KONSELING KOMPREHENSIF DALAM KAITANNYA DENGAN PROGRAM DAN STRATEGI KONSELING RELIGIUS - Liza Fidiawati; Asmadin Simarmata; Yulia Roza (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This research is motivated by a paradigm shift in guidance and counseling towards a comprehensive approach. In this regard, religious counseling programs and strategies theoretically have goals that align with the focus of comprehensive guidance and counseling. The purpose of this study is to gain a better understanding of counselors and comprehensive counseling in relation to religious counseling programs and strategies. This research method uses a systematic literature review approach where data is collected from various sources, including books, journals, research reports, and articles about comprehensive counseling and religious counseling. Reference data is sorted based on periodization, keywords, and limitations. The results of the study show that religious counseling programs and strategies